1
$\begingroup$

I am trying to derive the following reduction formula for integrating $\int{\frac{1}{(x^2 + a^2)^n}}dx, n,a>0$: $$I_n = \frac{1}{2a^2(n-1)}\left(\frac{x}{(x^2 + a^2)^{n-1}} + (2n-3)I_{n-1} \right)$$ So far I got $$\int{\frac{1}{(x^2 + a^2)^n}}dx = \frac{x}{(x^2 + a^2)^n} + 2n\int{\frac{x^2}{(x^2 + a^2)^{n+1}}}dx$$ and $$I_n = \frac{x}{(x^2 + a^2)^n} + 2nI_n - 2na^2I_{n+1} \Rightarrow I_n = \frac{1}{2a^2(n-1)}\left(\frac{x}{(x^2 + a^2)^{n-1}} + (2n-3)I_{n-1} \right)$$ but I'm struggling with the step in between: $$\int{\frac{x^2}{(x^2 + a^2)^n}}dx = I_n - a^2I_{n+1}$$

$\endgroup$
  • $\begingroup$ You have an ordinary identity: $\frac{x^2}{(x^2 + a^2)^{n+1}}= \frac{1}{(x^2 + a^2)^n} - a^2\frac{1}{(x^2 + a^2)^{n+1}}$... Are you sure the exponent in the first integral is $n$ and not $n+1$? $\endgroup$ – user491874 Feb 12 '18 at 20:25
  • $\begingroup$ Also, $n=0$: $\int{x^2dx}=\int{dx}-a^2\int{\frac{1}{x^2+a^2}dx}$ doesn't seem likely to hold, e.g. for $a=1$ you would have $\frac{x^3}{3}=x-\arctan x+C$... $\endgroup$ – user491874 Feb 12 '18 at 20:28
  • $\begingroup$ @user8734617 it holds for n>0, I added a clarification, thank you. $\endgroup$ – ZyTelevan Feb 12 '18 at 20:31
  • $\begingroup$ That equation doesn't hold for $a=0$ $\endgroup$ – Jose Lopez Garcia Feb 12 '18 at 20:34
1
$\begingroup$

$$\frac{1}{(x^2+a^2)^{n}}-\frac{a^2}{(x^2+a^2)^{n+1}}=$$ $$\frac{x^2+a^2}{(x^2+a^2)^{n+1}}-\frac{a^2}{(x^2+a^2)^{n+1}}=$$ $$\frac{x^2+a^2-a^2}{(x^2+a^2)^{n+1}}=$$ $$\frac{x^2}{(x^2+a^2)^{n+1}}\neq\frac{x^2}{(x^2+a^2)^{n}}$$

$\endgroup$
  • $\begingroup$ Oh. I tried integrating by parts again and u-substitution, but missed something that elementary, thank you! $\endgroup$ – ZyTelevan Feb 12 '18 at 20:35
  • $\begingroup$ @ZyTelevan You're welcome. $\endgroup$ – Botond Feb 12 '18 at 20:36
0
$\begingroup$

Let $a\neq0$, $n\in\mathbb{N}$ and define, $$I_n:=\int{\frac{dx}{(x^2+a^2)^n}}$$

So, If we use integral by parts, we have $$I_n = \frac{x}{(x^2+a^2)^n}+2n\int{\frac{x^2}{(x^2+a^2)^{n+1}}dx}\qquad(*)$$

On the other hand, $$I_n=\int{\frac{x^2}{(x^2+a^2)^{n+1}}dx}+a^2\int{\frac{dx}{(x^2+a^2)^{n+1}}}=\int{\frac{x^2}{(x^2+a^2)^{n+1}}dx}+a^2I_{n+1}\qquad(**)$$

Now using $(*)$ and $(**)$, follows that $$I_n=\frac{x^2}{(x^2+a^2)^{n}}+2n(I_n-a^2I_{n+1})\implies I_{n+1}=\frac{1}{2a^{2}n}\left(\frac{x}{(x^2+a^2)^n}-(1-2n)I_n\right)$$

In particular, if we take $n-1$, we have

$$I_n=\frac{1}{2a^{2}(n-1)}\left(\frac{x}{(x^2+a^2)^{n-1}}-(3-2n)I_{n-1}\right)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.